Exploring the Nexus of Capital Market and Investor Behaviour: A Systematic Literature Review - Gokhale, Gautam Milind; Mittal, Ankur (International Journal of Economics and Financial Issues, 2024)
This review paper delves into the intricate interplay between capital markets, investor protection, portfolio strategies, and behavioural aspects in investments. The VOSviewer 1.6.19 software is utilised to perform a bibliometric analysis and a exhaustive systematic literature review on a sample of 248 papers published in journals in Web of Science databases. Our comprehensive analysis reveals the emergence of key themes, shedding light on the critical role of behavioural finance in shaping investment choices and outcomes. We explore how investor behaviour often deviates from traditional models of market efficiency and how these deviations impact portfolio construction and investment strategies. Our paper contributes to a deeper comprehension of the complexities that drive investment decisions and helps academics, society, investors, and regulators by providing a structured analysis of literature strands. Builds a basis for better regulation and protection of investors in the capital markets, with relevant information for future studies on investor behaviour.